Factors of Cataractogenesis in Laser Corneal Refractive Surgery - I. M. Kornilosvskiy (Oftalʹmologiâ)
Purpose: to consider the main factors that stimulate cataractogenesis and the earlier development of cataracts after laser refractive surgery of the cornea. Patients and methods. The clinical material covers observations of the condition in more than 10 thousand eyes from 1 year to 20 years, after various laser refractive corneal operations (PRK, TransPRK, LASIK, FemtoLASIK). Results. Risk factors for cataractogenesis included high initial ametropia, accommodation disturbance, age, and increased external UV exposure. Clinical observations have shown that with laser correction of high degrees of ametropia, the number of cataractogenesis risk factors and their total value increased. Any laser refractive corneal surgery was accompanied by oxidative stress in all structures of the anterior eye and aseptic inflammatory response. The cornea thinning after refractive surgery increased the external UV load on the lens and created the conditions for the accumulation in it of an excessive amount of peroxide radicals. This was one of the important factors predisposing to the earlier development of cataracts. Conclusion. For clinically significant early cataract development after laser refractive corneal surgery, a combination of several cataractogenic factors is needed, such as the degree of severity of oxidative stress in the anterior eye tissue in the early postoperative period, cornea thinning, high corrective ametropia, lack of accommodation, and the patient age over 40 years old.